Antimicrobial susceptibility of Enterococcus spp. Isolated from different clinical sources in Kirkuk provency - Shareef, Hajir Ali; Abdullah, Shara Najmalddin (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
One of the most important problems confronts hospitals is the strains emergence  of Enterococcus spp. with multiple resistance to antibiotics, which propel researchers to modify or produce new antibiotics or combination between two antibiotics so that to be more effective against Enterococcus . This study was aimed to susceptibility some of local Enterococcus spp. Isolates with of 21 antibiotic using  disc diffusion method. The results showed absolute resistant 100% toward (Cephalexin , Gentamycin , Amikacin ,Erythromycin and Nalidixic acid), while showed a high sensitivity toward (Vancomycin and Impenem ) at percentage of 92.3% for each . Also highly inhibitory activity were observed by using penicillins antibiotics groups against most Enterococcus  isolates . which contribute to that non of the isolates showed it is ability to produce beta â€“ lactamase enzymes by iodometric tube method. Also susceptibility to some new and synergetic antibiotic like Gentamicin High level(synergy), Streptomycin High level (synergy), Linezolid, Tigecycline, Levofloxacin, Quinupristin /Dalfopristin was conducted by Vitek-2 system. the results showed the absolute sensitivity (100%) of isolates toward ( Linezolid and Tigecycline). All isolates showed multiple â€“resistant prescription to antibiotics , the number of antibiotics that every isolates resisted range between 6-12 antibiotic .